Association between perceptions of antiretroviral drug use and medication adherence in patients with human immunodeficiency virus - Muthmainnah; Katu, Sudirman; Tabri, Nur Ahmad; Syamsuddin, Saidah; Bakri, Syakib; Seweng, Arifin (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The effectiveness of antiretroviral therapy (ART) is determined by both antiretroviral (ARV) drugs and patient adherence. Positive perceptions of ART among people living with HIV and AIDS (PLHIVs) are crucial for maintaining good adherence; thus, negative beliefs about ARV drugs can result in lower ART effectiveness. This study analyzed the association between perceptions of ARV drug use and other medication adherence factors in patients with HIV. Methods: This observational, cross-sectional study included 102 PLHIVs to retrospectively assess adherence to ART through self-reports of patients while they were receiving ART. Perceptions of ARV drug use were evaluated with the Beliefs about Medicines Questionnaire. Statistical analysis was performed with the chi-square test, independent t-test, and Mann-Whitney test. Statistical significance was described as a p-value of